WACANA INDONESIA MAJU DALAM PIDATO PRESIDEN JOKO WIDODO - Hartanto, Bobie; Frederik Masri Gasa; Gamal Kusuma Zamahsari (Unika Santu Paulus Ruteng, 2021)
The text of Joko Widodo's speech when he was inaugurated as President of the Republic of Indonesia in 2019-2024 represents a five-year work plan and at the same time building Indonesia's advanced discourse. Thus, this study aims to examine and deepen the discourse using the Norman Fairclough critical discourse analysis framework. This study found that at the level of text analysis, Joko Widodo chose to use figures of speech or imagery as well as the interpretation of certain parts as the guardians of his intentions or ideas. Then at the level of discourse practice analysis, researchers found that there was a link between Joko Widodo's life experience and the direction of his policy despite positive and negative reactions to the content of the speech. Finally, at the level of analysis of sociocultural practices, researchers found that the text of Joko Widodo's speech departed from the condition of the Indonesian people during 2014 to 2019